Rural labour force transition and patterns of urbanization in China - United Nations (Asia-Pacific Population Journal, 1989)
Urbanization is characterized by the movement of people from rural areas to urban areas (Kupper and Kupper, 1985, p. 874). The term urbanization refers to such a redistribution of population as a demographic phenomenon, and the changing morphological structure of urban agglomerations and their development as social phenomena. The migration of populations links the rural areas with urban areas and is affected by “push” forces from rural areas and “pull” forces from urban areas. Different degrees of these forces determine the different pace, patterns and processes of migration and urbanization and the transition of populations.